The scope of the application of civil law under the institution of the person obligated to return the property benefits (art. 91a of the Code of the Criminal Procedure) – selected issues (Discourse of Law and Administration, 2022)
The institution of the person obligated to return the property benefits was previously regulated in art. 52 of the Penal Code and art. 16 of the Code of Criminal Procedure. These provisions were repealed, but after about two years the legislator returned to the mentioned solution in art. 91a and art. 415a of the Code of Criminal Procedure. In comparison to the previous regulation, the legislator modified the terms of liability, the powers and duties of the entity and the procedural aspects of adjudicating the liability of the entity. The legislator also formed in detail the scope of application of civil law under the institution of the person obligated to return the property benefits. The purpose of this article is to indicate to what extent civil law will be applied in selected areas of the commented institution.
Keywords: return of property benefits; entity obligated to return the benefits; benefits from commission of a crime; return of undue benefits; forfeiture of property benefits